The COVID-19 with Gastrointestinal Symptoms: A Case Report - Eka Surya Nugraha; Davin Takaryanto; Susantina Prodjosoewojo; Nenny Agustanti (The Indonesian Society for Digestive Endoscopy, 2020)
The COVID-19 mostly manifested as fever and pulmonary symptoms, but recent evidence demonstrated the frequent gastrointestinal symptoms in particular moderate to severe disease. Here, we present a case of a 51-years old man with confirmed COVID-19 diagnosis who was admitted with profuse acute diarrhea and nausea. He previously had a mild fever, cough, and shortness of breath. Administration of oseltamivir, levofloxacin, and chloroquine sulfate exaggerated vomiting, nausea, and increased serum level transaminase. After withdrawal, the gastrointestinal symptoms were relieved gradually. Adequate supportive treatment and fluid therapy ceased diarrhea and led to the negative result of the nasal swab RT-PCR COVID-19 after seven days.